Taxonomic notes in Meriania (Melastomataceae) from the Brazilian Atlantic Forest, including a new species, a resurrected one and a new synonym - Goldenberg, Renato; Meyer, Fabrício S.; Michelangeli, Fabián A. (Phytotaxa, 2020)
We present a new species, a new synonym, the resurrection of a species that has been synonymized before, updates on the distribution of three species, and lectotypifications for two species of Meriania from the Brazilian Atlantic Forest. Meriania baumgratziana is a new species apparently restricted to montane areas in the western portion of the state of Rio de Janeiro. It can be recognized by the sessile to subsessile leaves, these lanceolate, elliptic lanceolate or oblong-lanceolate, with cordate to cordulate, amplexicaul bases (seldom narrowly round), the abaxial surface in young leaves with the union of the primary and the inner pair of secondary veins with a membrane forming pocket domatia, these with trichomes emerging from the inside, then in older leaves the membranes frequently enlarged, globular, these hypertrophied structures sometimes caducous, or easily removed by friction, and by the pendulous inflorescences with 4-merous flowers. Meriania paratyensis Chiavegatto & Baumgratz is synonymized under M. sanchezii R.Goldenb., which in turn is resurrected from what we understand as a mistaken synonymy under M. paniculata DC. We present a discussion and illustrations of leaves and fruits, in order to explain these changes and compare all these three species, plus a fourth similar species, M. glabra (DC.) Naudin. The distributions of Meriania calyptrata (Naudin) Triana and M. sanchezii are updated, the former with the inclusion of specimens collected in the western tip of the state of Rio de Janeiro (it was previously recorded only for eastern São Paulo), and the latter in the exactly opposite way, with new records from Rio de Janeiro added to the previously known specimens from São Paulo. Finally, lectotypes are designated for Meriania calyptrata and M. glabra (DC.) Naudin (this superseding a previous, unnecessary designation of a neotype).